Exploring the Use of Artificial Intelligence in Teaching Chemistry at Higher Education Institutions: A Systematic Analysis and Student Perspectives (Journal of Educational Sciences, 2025)
The article discusses the impact of technology development and the increasing availability of digital educational resources on improving the quality of learning and transforming traditional pedagogical approaches to teaching chemistry. The integration of artificial intelligence (AI) into the process of teaching chemistry opens up new opportunities for personalizing learning, increasing student motivation and developing their analytical and research skills. AI technologies allow effectively adapting the teaching material, optimizing the solution of practical problems and providing a deeper assimilation of the discipline content.The present article is devoted to the system analysis of AI application in chemistry teaching in higher education institutions. The key aspects of AI integration into the educational environment are considered, its advantages and possible challenges are identified. The systematic analysis of scientific literature on the topic was conducted using specialized keywords on Scopus and Google Scholar databases, which allowed identifying current trends and approaches to the application of artificial intelligence in the educational sphere. The empirical part of the study consisted of the results of a survey of 194 students from three leading universities in the South Kazakhstan region, aimed at studying the perception and experience of using AI in the process of studying chemistry. The obtained data indicate the widespread use of AI tools in chemistry teaching and confirm their high potential under the condition of their purposeful and pedagogically sound integration into the learning process.Key words: teaching chemistry, artificial intelligence (AI), machine learning, neural networks, ChatGPT, modern teaching tools, AI integration in education.